2011
DOI: 10.1007/s11746-011-1876-y
|View full text |Cite
|
Sign up to set email alerts
|

Valorization of Beef Tallow by Lipase‐Catalyzed Interesterification with High Oleic Sunflower Oil

Abstract: Although beef tallow (BT) has been considered a hard low-trans fat convenient to be used in several bakery applications, it has some undesirable characteristics like fatty acid composition, crystallization behavior, graininess formation and poor plastic range. This work studied the modification of BT by blending at different percentages with high oleic sunflower oil (HOSFO) followed by the enzyme-catalyzed interesterification of the blends. The reduction in the solid fat content achieved by the simple blending… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
14
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 16 publications
6
14
1
1
Order By: Relevance
“…The contribution of this group of TAG was exclusive from BT, reason why this effect was expected. The same was also observed in previous studies with high oleic sunflower oil (HOSFO) (Segura et al, 2011a).…”
Section: Triacylglycerols Compositionsupporting
confidence: 88%
“…The contribution of this group of TAG was exclusive from BT, reason why this effect was expected. The same was also observed in previous studies with high oleic sunflower oil (HOSFO) (Segura et al, 2011a).…”
Section: Triacylglycerols Compositionsupporting
confidence: 88%
“…The main FA in HOSO was oleic acid (87.4%), and the amount of UFA was 93.1%. Segura et al found similar results for this raw material . In FHSO, the predominant FA was stearic acid (86.6%), followed by palmitic acid (11.5%), both long‐chain SFA, which comprised 99.7% of its structure.…”
Section: Resultssupporting
confidence: 60%
“…In particular, the temperature range in which SFC of IF significantly decreased shifted to 10-20 in the low temperature range from 42.84 to 23.73 , which may attributed to the saturated fatty acid composition in TAG i.e., the content of SSS decrease, SUS and SUU increase had changed 29,30 . It was demonstrated that what was referred to as the desirable plastic range of fats should have the properties that the SFC contains roughly 15-35 solids at 25 31 . So with a wider plastic range and an ideal SFC curve, IF is suitable for plastic fats application.…”
Section: Solid Fat Contentmentioning
confidence: 99%